Analysis and design of DevOps (DevSecOps) IT processes in the automotive industry - Koťara, Tomáš (2024)
The automotive industry is undergoing a rapid transformation, driven by the development of self-driving cars, electric vehicles, and other new technologies. This transformation is putting a strain on traditional IT processes, which are often slow and siloed. DevOps (DevSecOps) is a set of practices that aims to bridge the gap between development and operations and to integrate security into the software development lifecycle. This master thesis will analyse and design DevOps (DevSecOps) IT processes for the automotive industry. The thesis will begin by reviewing the current state of IT in the automotive industry and identifying the challenges that need to be addressed. The thesis will then discuss DevOps (DevSecOps) principles and practices and how they can be applied to the automotive industry. The main body of the thesis will present a detailed design for DevOps (DevSecOps) IT processes for the automotive industry and draw a process map of how the DevSecOps department works. The design will cover all aspects of the software development lifecycle, from planning and requirements gathering to deployment and support. The design will also address the unique challenges of the automotive industry, such as safety and security requirements. The thesis will conclude by evaluating the proposed design and discussing the potential benefits and risks of implementing DevOps (DevSecOps) in the automotive industry. The thesis will also identify areas for future research.